Genealogies of Testimony in Post-Dictatorship Argentine Literature: María Negroni's La Anunciación - Venturini, Ximena (Escritura e Imagen, 2024)
The article carries out a genealogy of the testimonial genre based on an analysis of thenovel La Anunciación by the Argentine writer María Negroni. Some of Longoni’s (2007) ideas onthe testimonial genre in contemporary Argentina and the suspicion that fell under the survivors willbe applied, as well as the concept of “threshold” coined by Forcinito (2012). On the other hand, thetestimonial genre will be studied in relation to the phenomena of the tension between mourning andnarration that Avelar (1999) identified in post-dictatorship literatures in the Southern Cone. These ideaswill be applied to the novel analyzed in this paper.
Keywords: post-dictatorship; María Negroni; testimonial genre; Cono Sur; Argentine literature